Effects of Sirolimus Treatment on Fetal Hemoglobin Production and Response to SARS-CoV-2 Vaccination: A Case Report Study - Maria Rita Gamberini; Cristina Zuccato; Matteo Zurlo; Lucia Carmela Cosenza; Alessia Finotti; Roberto Gambari (Hematology Reports, 2023)
The β-thalassemias are a group of monogenic hereditary hematological disorders caused by deletions and/or mutations of the β-globin gene, leading to low or absent production of adult hemoglobin (HbA). For β-thalassemia, sirolimus has been under clinical consideration in two trials (NCT03877809 and NCT04247750). A reduced immune response to anti-SARS-CoV-2 vaccination has been reported in organ recipient patients treated with the immunosuppressant sirolimus. Therefore, there was some concern regarding the fact that monotherapy with sirolimus would reduce the antibody response after SARS-CoV-2 vaccination. In the representative clinical case reported in this study, sirolimus treatment induced the expected increase of fetal hemoglobin (HbF) but did not prevent the production of anti-SARS-CoV-2 IgG after vaccination with mRNA-1273 (Moderna). In our opinion, this case report should stimulate further studies on β-thalassemia patients under sirolimus monotherapy in order to confirm the safety (or even the positive effects) of sirolimus with respect to the humoral response to anti-SARS-CoV-2 vaccination. In addition, considering the extensive use of sirolimus for the treatment of other human pathologies (for instance, in organ transplantation, systemic lupus erythematosus, autoimmune cytopenia, and lymphangioleiomyomatosis), this case report study might be of general interest, as large numbers of patients are currently under sirolimus treatment.